Peran Kinerja sebagai Mediasi dalam Hubungan Kapabilitas Finansial dan Orientasi Kewirausahaan terhadap Keunggulan Bersaing: (Studi pada UMKM Perdagangan Kota Tasikmalaya) - Cindi Ibriani; Azizah Fauziyah; Ismail Yusuf (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
The purpose of this study is to examine the influence of financial capability and entrepreneurial orientation on sustainable competitive advantage and the performance of trade-based MSMEs in Tasikmalaya City. The research method employed is a quantitative approach, with data collected through questionnaires distributed to 100 trade MSME actors in Tasikmalaya City. The Structural Equation Modeling (SEM) approach was employed to analyze the data and examine the relationships among the research variables.. The results show that financial capability does not affect sustainable competitive advantage, but it has a significant effect on MSME performance. Entrepreneurial orientation has a significant effect on both sustainable competitive advantage and MSME performance. Sustainable competitive advantage also significantly affects the performance of trade MSMEs in Tasikmalaya City. From the indirect effect analysis, it was found that financial capability and entrepreneurial orientation significantly influence sustainable competitive advantage through MSME performance. The findings are expected to enhance comprehension of the contributing factors to competitive advantage and the performance of MSMEs, as well as strategic recommendations for business actors and policymakers to enhance sustainable business competitiveness.